On the Effectiveness of Group Cognitive-Behavioral Therapy and Logotherapy in Reducing Depression and Increasing Life Expectancy in Drug Addicts - Mohammad Khaledian; Mohammad Ali Mohammadifar (Drug Control Headquarters, Research and Education Office, 2016)
Objective: This study was an attempt to compare the effectiveness of group cognitive-behavioral therapy and logotherapy therapy in Reducing Depression and Increasing Life Expectancy in Drug Addicts. Method: This was an experimental study along with pretest/posttest and control group. All the addicts referring to one of the methadone addiction treatment centers in Qorveh City (Naikoo Salamat Center) in 2013 constituted the population of the study. Initially, 60 students were selected by simple random sampling. Then, 30 participants were randomly divided into two experimental groups and one control group based on their scores on Beck Depression Inventory and Snyder’s Life Expectancy Test. One of the experimental groups received 10 logotherapy sessions and the second experimental group received 13 sessions of group cognitive-behavioral therapy. This is so while the control group received no intervention. Results: The results showed that there was not any significant difference between group cognitive behavioral therapy and logotherapy in reducing depression. However, group cognitive behavioral therapy was found to be more effective in increased life expectancy than logotherapy. Conclusion: The results contain practical implications.